2015
DOI: 10.1038/bjc.2015.326
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutations are frequent and show association with MED12 mutations in phyllodes tumors of the breast

Abstract: Background:Phyllodes tumors are rare fibroepithelial neoplasms of the breast, which carry the potential risk of local recurrence and metastasis. Phyllodes tumors share several histological features with fibroadenomas, and no widely accepted markers for distinguishing these lesions have been identified.Methods:We analyzed molecular abnormalities related to telomere elongation in tumors, including TERT promoter mutations, as well as loss of expression of ATRX and DAXX, in a total of 104 phyllodes tumors and fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 29 publications
4
79
6
Order By: Relevance
“…Our study differed from that of Yoshida et al in that the only TERT promoter mutation found in the 76 PTs analyzed here was the −124 C>T hotspot mutation, that the frequency of TERT promoter mutations in benign PTs in this study (7/40, 18%) was significantly lower than that reported by Yoshida et al (9/18, 50%, p = 0.02, Fisher's exact test) and that only 52% of the PTs harbouring TERT promoter mutations also displayed MED12 mutations in our study, as opposed to 97% of TERT mutant PTs reported by Yoshida et al ( p < 0.0001, Fisher's exact test). Most importantly, from a diagnostic perspective, the results of our study are fundamentally different from those of Yoshida et al with regard to the presence of TERT promoter mutations in fibroadenomas. Whilst four of the 58 (7%) fibroadenomas analyzed by Yoshida et al harboured the −124 C>T TERT promoter hotspot mutation, all of the 100 consecutive fibroadenomas analyzed here displayed wild‐type TERT .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study differed from that of Yoshida et al in that the only TERT promoter mutation found in the 76 PTs analyzed here was the −124 C>T hotspot mutation, that the frequency of TERT promoter mutations in benign PTs in this study (7/40, 18%) was significantly lower than that reported by Yoshida et al (9/18, 50%, p = 0.02, Fisher's exact test) and that only 52% of the PTs harbouring TERT promoter mutations also displayed MED12 mutations in our study, as opposed to 97% of TERT mutant PTs reported by Yoshida et al ( p < 0.0001, Fisher's exact test). Most importantly, from a diagnostic perspective, the results of our study are fundamentally different from those of Yoshida et al with regard to the presence of TERT promoter mutations in fibroadenomas. Whilst four of the 58 (7%) fibroadenomas analyzed by Yoshida et al harboured the −124 C>T TERT promoter hotspot mutation, all of the 100 consecutive fibroadenomas analyzed here displayed wild‐type TERT .…”
Section: Discussioncontrasting
confidence: 99%
“…harbouring TERT promoter mutations also displayed MED12 mutations in our study, as opposed to 97% of TERT mutant PTs reported by Yoshida et al [12] (p < 0.0001, Fisher's exact test). Most importantly, from a diagnostic perspective, the results of our study are fundamentally different from those of Yoshida et al [12] with regard to the presence of TERT promoter mutations in fibroadenomas.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…10,11 Finally, TERT promoter mutations and gene amplifications are absent or exceedingly rare in FAs, but recurrent in PTs, though significantly more frequent in borderline and malignant PTs than in benign PTs, suggesting that TERT genetic alterations might play a role in the progression from benign to malignant PTs. 8,10,12,13 …”
Section: Introductionmentioning
confidence: 99%